Coastal influence on microbiomes of the Southwest Atlantic Ocean - Cristiane C. Thompson; Diogo Tschoeke; Luciana Leomil; Lucas Freitas; Livia Vidal; Koko Otsuki; Claudia Omachi; Igor M. Venâncio; Yulin Zhang; Jiwen Liu; Xiao-Hua Zhang; Ana Luiza S. Albuquerque; et al. (Evolving Earth)
The possible influence of the continent on the microbiome of the Southwest Atlantic Ocean (SAO) is not yet fully known. The aim of the present study was to evaluate the metagenomic diversity of the SAO nearshore in different locations (e.g., rivers and upwellings) and offshore locations. The studied sites (n = 16) were clustered into four groups (G1-G4) according to the decadal sea surface temperature (SST) and levels of chlorophyll a (chl-a) (2007–2016). G1 (coastal upwelling) presented the highest chl-a values, G2 (shelf) had the highest SST, G3 (offshore north) had the lowest chl-a levels, and G4 (offshore south) was the coldest site. The higher nutrient levels may contribute to higher chl-a-based primary productivity and possibly higher bacterial productivity nearshore. The taxonomic and functional diversity of the total of 16 Illumina shotgun metagenomes were analysed (nearshore: 10, offshore: 6; mean ± standard deviation: 1.87 ± 0.41 million reads per sample). The SAO microbiomes were split into two groups: nearshore and offshore. The SAO coastal zone had higher abundance of picoplanktonic cyanobacteria (e.g., Prochlorococcus), copiotrophic bacteria (e.g., Alteromonas), chl-a photosynthesis, and metabolism of nitrogen and phosphorus. In clear contrast with offshore microbiomes, nearshore microbiomes were heterogenous as a possible effect of riverine runoff and the upwelling. G1 microbiomes had higher abundance of copiotrophic bacteria, while G2 had a higher abundance of Prochlorococcus, and G3 had a higher abundance of Pelagibacter. Offshore metagenomes (G3 and G4) had enrichment of proteorhodopsin light harvesting and sulfur metabolism, possible relevant processes in the SAO. Metagenome assembled genomes (MAGs) demonstrated significant novel microbiome diversity. The most abundant MAGs belong to Flavobacteria and Euryarchaeota. The discrimination of microbial populations and metabolisms in the four studied oceanographic groups provides a first glimpse on the microbial landscape in the SAO.